Sex Differences in Clinical Features of Early, Treated Parkinson’s Disease - Augustine, Erika F.; Pérez, Adriana; Dhall, Rohit; Umeh, Chizoba C.; Videnovic, Aleksandar; Cambi, Franca; Wills, Anne-Marie A.; Elm, Jordan J.; Zweig, Richard M.; Shulman, Lisa M.; Nance, Martha A.; Bainbridge, Jacquelyn; et al. (PLOS ONE, 2015)
Introduction To improve our understanding of sex differences in the clinical characteristics of Parkinson’s Disease, we sought to examine differences in the clinical features and disease severity of men and women with early treated Parkinson’s Disease (PD) enrolled in a large-scale clinical trial. Methods Analysis was performed of baseline data from the National Institutes of Health Exploratory Trials in Parkinson’s Disease (NET-PD) Long-term Study-1, a randomized, multi-center, double-blind, placebo-controlled study of 10 grams of oral creatine/day in individuals with early, treated PD. We compared mean age at symptom onset, age at PD diagnosis, and age at randomization between men and women using t-test statistics. Sex differences in clinical features were evaluated, including: symptoms at diagnosis (motor) and symptoms at randomization (motor, non-motor, and daily functioning). Results 1,741 participants were enrolled (62.5% male). No differences were detected in mean age at PD onset, age at PD diagnosis, age at randomization, motor symptoms, or daily functioning between men and women. Differences in non-motor symptoms were observed, with women demonstrating better performance compared to men on SCOPA-COG (Z = 5.064, p<0.0001) and Symbol Digit Modality measures (Z = 5.221, p<0.0001). Conclusions Overall, men and women did not demonstrate differences in clinical motor features early in the course of PD. However, the differences observed in non-motor cognitive symptoms suggests further assessment of the influence of sex on non-motor symptoms in later stages of PD is warranted.